PROBLEM-BASED LEARNING IN THE DIGITAL ERA: TECHNOLOGIES, CASES, AND PROSPECTS - Tastanov, M.G.; Tuktubayeva, S.A. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
The article explores the impact of digital technologies on problem-based learning, analyzing the most effective tools and their prospects in the educational process. Special attention is given to interactive platforms, artificial intelligence, gamification, and virtual reality. The study presents survey results of students and teachers regarding the role of technologies in education. Challenges of the digital era, such as digital inequality and the need to improve digital literacy, are discussed. The article concludes with the necessity of adapting educational programs and enhancing teachers' professional development.
Keywords: Problem-Based Learning (PBL); Digital technologies; Interactive platforms; Gamification; Virtual reality; Artificial intelligence (AI); Digital inequality; Digital literacy; Educational process; STEM laboratories